2021
DOI: 10.1007/s10096-021-04178-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sero-positivity for IgG, sequelae of respiratory symptoms, and abundance of malformed sperms in a patient recovered from severe COVID-19

Abstract: Patients with severe coronavirus disease in 2019 (COVID-19 pneumonia) may have many sequelae, which seriously affect their quality of life and work. Here, we report a case of infection in China, reviewed the course, treatment, and rehabilitation of a patient suffering from severe COVID-19 pneumonia, and collected his examination reports, including chest CT, laboratory examination results, lung function examination, sleep monitoring report, sex hormones, sperm morphology and activity. The patient’s antiviral im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…study by Zhu et al also reported long-term abnormal airway function for up to 11 months in a severe COVID-19 patient ( 44 ). However, because is a single case, this research does not provide conclusive evidence.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…study by Zhu et al also reported long-term abnormal airway function for up to 11 months in a severe COVID-19 patient ( 44 ). However, because is a single case, this research does not provide conclusive evidence.…”
Section: Resultsmentioning
confidence: 84%
“…Differently, Latronico et al showed that since residual abnormal chest-X ray findings were detected in about 70% of critically ill COVID-19 patients at 3 months, very few of them (∼12%) had persisting respiratory symptoms at 6 months ( 27). An anecdotal study by Zhu et al also reported long-term abnormal airway function for up to 11 months in a severe COVID-19 patient (44). However, because is a single case, this research does not provide conclusive evidence.…”
Section: Persistent Lung Symptoms and Dysfunctionsmentioning
confidence: 72%
“…Frequency of lung imaging abnormalities per different evaluation setting. References [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] are cited in the Supplementary Materials…”
mentioning
confidence: 99%
“…Several alterations such as azoospermia, oligozoospermia, criptozoospermia and teratozoospermia were found ( 35 , 48 , 51 , 67 ). Gacci et al ( 35 ) reported that 25.6% of patients developed some of these alterations and that concentration of sperm was lower in more severely will patients.…”
Section: Resultsmentioning
confidence: 99%